(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background Hemangiomas are vascular lesions frequently seen in the head & neck region. Lip is an important site for such lesions. Most of the hemangiomas are seen at birth or the neonatal age group. It is uncommon to see such a lesion in adults. They mostly present as soft, smooth lobulated masses. Patients with hemangioma of lip seek treatment for aesthetic alteration and functional limitations caused by the lesion. The various treatment options include surgical excision of the tumor, embolization, electrosurgery, cryosurgery, laser excision, steroid injection, or injecting sclerosing materials. Here we report two cases of lip hemangiomas in adults. Methods In the first case, a 34 years old man presented to ENT OPD with a painless progressively enlarging nodular growth in the vermilion border of lower lip appreciated for 2 months which was surgically excised using electrocautery. In the second case, a 58 years old man presented to ENT OPD with a painless progressively enlarging lobulated growth in the lower lip appreciated for 4 months which was surgically excised using electrocautery. Results Histopathological examination of resected specimen in both the cases confirmed the diagnosis as capillary hemangioma. Conclusion Hemangiomas should be kept as differential diagnosis of benign lesions of lip.